1995
DOI: 10.1139/b95-101
|View full text |Cite
|
Sign up to set email alerts
|

Calcium translocation, calcium oxalate accumulation, and hyphal sheath morphology in the white-rot fungusResinicium bicolor

Abstract: The white-rot fungus Resinicium bicolor was cultured on wood blocks in a modified soil block assay and was observed by environmental scanning electron microscopy and scanning electron microscopy. Resinicium bicolor was found to translocate calcium in mycelial cords in quantities greater than that found in the wood blocks and accumulated this calcium in the form of calcium oxalate. Calcium oxalate crystal clusters of mycelial cords were 3 × larger and far more numerous than the crystal clusters produced by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 22 publications
4
51
0
5
Order By: Relevance
“…The OA and OX data show an OX increment in W FA during incubation and a corresponding decrease in W, but the data cannot be explained by crystal formation in W FA alone. Many fungi, both brown-and white rot fungi can produce Ca-OX crystals that adhere to the hyphae (Connolly and Jellison 1995) and are located within the fungal sheath. It has been suggested that Ca-OX precipitation along the hyphae of fungi can be an intracellular, periplasmic, or intramural nucleation with subsequent exteriorisation of the growing crystals (Connolly and Jellison 1995).…”
Section: Analysis Of Oxalic Acid (Oa) and Oxalate (Ox)mentioning
confidence: 99%
See 1 more Smart Citation
“…The OA and OX data show an OX increment in W FA during incubation and a corresponding decrease in W, but the data cannot be explained by crystal formation in W FA alone. Many fungi, both brown-and white rot fungi can produce Ca-OX crystals that adhere to the hyphae (Connolly and Jellison 1995) and are located within the fungal sheath. It has been suggested that Ca-OX precipitation along the hyphae of fungi can be an intracellular, periplasmic, or intramural nucleation with subsequent exteriorisation of the growing crystals (Connolly and Jellison 1995).…”
Section: Analysis Of Oxalic Acid (Oa) and Oxalate (Ox)mentioning
confidence: 99%
“…Many fungi, both brown-and white rot fungi can produce Ca-OX crystals that adhere to the hyphae (Connolly and Jellison 1995) and are located within the fungal sheath. It has been suggested that Ca-OX precipitation along the hyphae of fungi can be an intracellular, periplasmic, or intramural nucleation with subsequent exteriorisation of the growing crystals (Connolly and Jellison 1995). The substrate pH modulation facilitates the activity of fungal extracellular enzymes that have pH optima below 5 (Punja et al 1985).…”
Section: Analysis Of Oxalic Acid (Oa) and Oxalate (Ox)mentioning
confidence: 99%
“…This latter procedure has been used to qualitatively identify the presence of oxalate in white rot fungus (Connolly and Jellison, 1995). The SIGMA method involves degradation of oxalate by oxalate oxidase and combining the degradation product, hydrogen peroxide, with two substrates that form a colored complex, measurable by colorimetry.…”
Section: Quantitative Determination Of Calcium Oxalate and Oxalate Inmentioning
confidence: 99%
“…Encrusted spines de veloped on the subicular hyphae of some species appear to be a reduced form of astrocystidia. For scanning electron micrographs of astrocystidia and crystal clusters, see Keller (1985) and Connolly and Jellison (1995).…”
Section: Morphological Studiesmentioning
confidence: 99%